Improved physical layer for energy-efficient M2M communications over cellular networks - Ming Liu; Crussiere, Matthieu; Helard, Jean-Francois (2015 23rd International Conference on Software, Telecommunications and Computer Networks (SoftCOM), 2015)
The existing GSM networks are promising candidates to enable the machine-to-machine (M2M) communications due to their global deployment. However, these networks are initially designed for mobile telephony, and need to be renovated to adapt to the new M2M applications. In this paper, we address the perspective of upgrading the channel coding scheme of the GSM networks for the M2M communications. Concretely, we investigate two possible solutions, namely concatenated codes (convolutional and Reed-Solomon) and Turbo codes. It is shown that the Turbo coding scheme can simultaneously improve both the service coverage and the energy efficiency performance, and is therefore suitable for the future M2M applications. Finally, it is demonstrated that the enhanced channel coding scheme leads to the reduced energy consumption, or equivalently a longer battery life, in the typical M2M scenarios.